Pengaruh Pemberian Sayur Daun Pepaya terhadap Kelancaran ASI Ibu Nifas di Wilayah RS Haji - Marsilia, Imelda Diana; Sastrawatii, Sastrawatii; Nurulicha, Nurulicha (Universitas Baiturrahim, 2024)
Success in exclusive breastfeeding is influenced by the smooth production of breast milk. As many as 60% of postpartum mothers at the Jakarta Hajj Hospital in 2022 experienced breast milk insufficiency. Food intake is one of the indirect factors that can affect the milk production of a nursing mother. Consumption of papaya leaf vegetables is an effort to increase the smoothness of breast milk, there is papain in papaya leaf sap which can increase milk production. The purpose of the study was to determine the effect of giving papaya leaf vegetables to the smooth breastfeeding of postpartum mothers in the Haji Hospital area. This study was a quasi-experimental, with one group pretest-posttest design without control. The study was conducted at the Hajj Hospital Jakarta. The population in the study was 33 postpartum mothers. The total sample is 30 people, with accidental sampling technique. Data analysis used univariate and bivariate Wilcoxon signed rank test. The results showed that there was an effect of giving papaya leaf vegetables to the smoothness of postpartum mother's milk, the average value was 1.3 before being given papaya leaf vegetables and increased with an average value of 4.4 after the intervention of giving papaya leaf vegetables. Suggestions that consumption of papaya leaf vegetables can be one of the efforts to increase milk production for breastfeeding mothers.